Composite stimulation technology for improving fracture length and conductivity of unconventional reservoirs - Wang, Yang; Lv, Zefei (Frontiers in Physics, 2023)
Carbonate reservoir has strong heterogeneity, and the distribution of porosity and permeability is very different. Acid fracturing is an important technology to increase the natural gas production in carbonate gas reservoirs. For ultra-high temperature reservoirs, the rapid increase of acid rock reaction speed leads to the significant reduction of effective distance of acid fluid and fracture conductivity, which restricts the increase of natural gas production in ultra-high temperature carbonate gas reservoirs. To solve the above problems, a compound acid fracturing method is proposed, which first uses proppant to propping the tip of the fracture, and then uses gelling acid to corrode the middle and rear sections of the fracture. According to the fracture conductivity test experiment and proppant migration experiment, when 40/70 mesh ceramsite and 100 mesh ceramsite are mixed at a mass ratio of 1:4, the fracture conductivity can reach 21.8μm·cm2 under an effective closure pressure of 60MPa, which is 123% higher than the fracture conductivity corroded by gelling acid. The gel is used to carry 40/70 mesh and 100 mesh ceramsite, and the equilibrium height of the sand dike can reach 38cm. At the same time, the sand dike formed by ceramsite with different particle sizes is more gentle than that formed by proppant with single particle size, and the ceramsite has better migration ability to the fracture tip. The compound acid fracturing technology has been applied in the ultra-high temperature and low permeability carbonate gas reservoir for six wells, and the gas production of the gas well after acid fracturing is 650% higher than that of the gelling acid fracturing, which has achieved good stimulation effect.